Alkaloids of catharanthus roseus and their hypoglycemic activity / Tiong Soon Huat - Tiong, Soon Huat (2014)
Catharanthus roseus is a medicinal shrub plant used in traditional medicine treatment by local in India, South Africa, China and Malaysia for diabetes. Six known alkaloids and one new alkaloid namely, vindoline, vindolinine, perivine, vindorosine, vindolicine, serpentine and vindogentianine were isolated and identified from dichloromethane extract of Catharanthus roseus’ leaves. The leaves dichloromethane extract of Catharanthus roseus and alkaloids were not cytotoxic towards β-TC6 cells at 50.0 μg/mL except vindolinine and perivine with IC50 at 20.5 ± 3.6 and 46.7 ± 4.4 μg/mL. All five alkaloids tested showed higher glucose uptake in β-TC6 cells at treatment of 12.5 μg/mL and 25.0 μg/mL compared with untreated cells. Vindorosine, vindolicine and vindogentianine were shown to possess in vitro hypoglycemic activity for the first time. Vindolicine demonstrated highest hypoglycemic activity in glucose uptake and PTP-1B inhibition assay. The isolated alkaloid compounds could be responsible for the antidiabetic effect in Catharanthus roseus extracts and provide an explanation to its traditional usage.